(untitled) (Education in the 21st Century, 2023)
The purpose of the study is to characterize peculiarities of foreign language training in technical higher education institutions in the conditions of modernization of higher education in Ukraine based on the analysis of modern research. The relevance of the raised problem is determined by the fact that the modernization of higher education of Ukraine, its entry into the European and world educational space is not possible without a significant increase in the quality of students’ foreign language training, in particular, technical higher education institutions. The novelty of the research lies in the fact that the role of "Common European Framework of Reference for Languages: Learning, Teaching, Assessment" in the restructuring of national standards of foreign language training has been indicated. It is underlined that integrated learning major and foreign language, which is based on the study of professional disciplines in inseparable unity with mastering a foreign language and involving intra- and interdisciplinary connections, is a necessity and a significantly new step to improve and modernize students’ foreign language training in technical higher education institutions. It is highlighted that the implementation of integrated learning major and foreign language in the educational space of technical higher education institutions strengthens the practical component of foreign language training. It is stated that modern realities of foreign language training are focused on attracting innovative methods and approaches to learning, based on students’ interaction and modelling of their future professional activity. Attention is paid to the need to reorient the educational process to the future specialist’s personality, student-centeredness. Conclusions. As a result of the research, features of foreign language training in technical higher education institutions of Ukraine in the conditions of modernization of higher education have been identified. It is noted such new features as consistency and synchronization of requirements for foreign language training through the implementation of "Common European Framework of Reference for Languages: Learning, Teaching, Assessment"; integrated learning major and foreign language; strengthening the practical component of students’ foreign language training; reorienting the educational process to the future specialist’s personality, student-centeredness and others. It is revealed that further scientific research can be devoted to the study of innovative methods and approaches to learning, which are based on students’ interaction and contribute to the modelling of future professional activity.